2005
DOI: 10.1111/j.1600-0633.2005.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and reproduction of the African bonytongue Heterotis niloticus in the Sô River‐floodplain system (West Africa): implications for management

Abstract: Population structure and reproduction of the African bonytongue Heterotis niloticus in the Sô River-floodplain system (West Africa): implications for management Un resumen en espan˜ol se incluye detra´s del texto principal de este artı´culo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 15 publications
(19 reference statements)
4
39
0
1
Order By: Relevance
“…Seasonal flooding facilitates dispersal of H . niloticus within the Ouemé–Sô River floodplain system (Adite et al , ); thus, low levels of population genetic differentiation for this fish are expected within this system.…”
Section: Pair‐wise Fst Between the Heterotis Niloticus Localities (Sementioning
confidence: 99%
“…Seasonal flooding facilitates dispersal of H . niloticus within the Ouemé–Sô River floodplain system (Adite et al , ); thus, low levels of population genetic differentiation for this fish are expected within this system.…”
Section: Pair‐wise Fst Between the Heterotis Niloticus Localities (Sementioning
confidence: 99%
“…The highest correlation was found between fecundity and gonad mass in the headwaters and between fecundity and body length in the flood area. Several studies have identified a positive relationship between the number of oocytes and fish size (Adite et al, 2006;Brickle et al, 2005;Magalhães et al, 2003;Mazzoni & Silva, 2006;Moffett et al, 2006;Sato et al, 2006;Tarkan, 2006;Martins-Queiroz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, as digestive tract becomes well developed, Heterotis takes advantage to other available resources such as detritus and seeds to rapidly satisfy his high protein and energetic requirements (Steingrimsson and Gislason, 2002) [31]. The low negative correlations of standard length and gut length with microcrustacea compared to those with aquatic insects were probably due to the presence of gill rakers (42 -94 rakers on the first branchial arch) (Moreau, 1982) during the whole life of Heterotis, which facilitate sieving of zooplankton and other microcrustacea regardless of age or size (Adite et al, 2006) [8,32]. For example, a 605 mm specimen, collected from Lake Hlan have consumed 100% (volume = 3 ml) of microcrustacea, mainly cladoceran and copepod.…”
Section: Ecomorphological Patternsmentioning
confidence: 99%
“…In addition to the broader diet breadths, the trophic plasticity behavior depicted is an advantage for the survival, the conservation and the aquaculture development of Heterotis because enable the species not only to colonize and to adapt to unstable and changing aquatic habitats, but also to invade and to well establish in many habitats with different features (physical characteristics; food availability, niche breadths and niche overlaps), such as freshwater lakes, swamps, inundated plains, streams, rivers and fish ponds capable of varying water level in order to stimulate gonad maturation and to insure reproduction success [32,35].…”
Section: Trophic Plasticity Behavior: Implications For Species Consermentioning
confidence: 99%